Overexpression of HSP70 attenuates sarcopenia by suppressing the expression of miR‐133b - Tábata L. Nascimento; Ruben Mestril; Elen H. Miyabara (Wiley, 2020)
Abstract Background The aim of the present investigation is to evaluate the effect of the overexpression of inducible 70‐kDa heat shock protein (HSP70) on sarcopenic muscles of aged mice. Methods Tibialis anterior muscles of aged and young transgenic mice overexpressing HSP70 and wild‐type mice were evaluated. Old mice were treated with the HSP inducer O‐[3‐piperidino‐2‐hydroxy‐1‐propyl]‐nicotinic amidoxime (BGP‐15) for 10 days, and their muscles were analysed. Results Old HSP70 transgenic mice presented a less pronounced decrease in myofiber size, lower protein levels of Foxo3a, and a spared increase in miRNA‐133b expression when compared with old wild‐type mice. Moreover, in BGP‐15‐treated old mice, the reduction in myofiber size was less intense, and the decline in muscle specific force was attenuated. Conclusions These results suggest that HSP70 overexpression attenuates sarcopenia in old mice, and this effect may be mediated by miR‐133b down‐regulation. In addition, BGP‐15 treatment may be a useful strategy to mitigate the effects of sarcopenia in old mice.